Pembuatan Logo sebagai Merek dari Kerajinan Pipiti untuk Souvenir dalam Mendukung Desa Wisata Kawungluwuk - Najwa Abdillah; Syafiqah Mahdiah Dai; Rinie Octaviany Hasan; Nining Nining (Universitas Pahlawan Tuanku Tambusai, 2026)
This activity strengthens pipiti handicrafts' identity as a signature souvenir of Kawungluwuk Tourism Village through branding development, including a brand name, logo, and philosophy based on local wisdom. The partners' challenge is that pipiti products lack a clear brand identity, resulting in limited appeal and competitiveness. The activity used Participatory Action Research (PAR), emphasizing active partner participation from problem identification to implementation. The stages included designing the brand name, logo, and philosophy; branding education; and handover of design results. The branding produced the name